Spatio-temporal dynamic evolution characteristics and driving mechanism analysis of urban pseudo human settlements - Li, Hang; Lou, Lin; Wang, Yadan; Tian, Shenzhen; Yang, Jun; Cong, Xueping (Frontiers in Earth Science, 2024)
Pseudo human settlements in the information age is an important part of human settlements geography, which has a comprehensive and profound impact on urban production, life and ecology in China and even the world, but the existing research on pseudo human settlements is still unclear, and cannot meet the requirements of China’s “digital-realistic fusion”, “network power” and the construction of a beautiful China. Therefore, this paper starts from the perspective of pseudo, based on the theory of the coupling system of human settlements, and applies the entropy weight method, coupling coordination model, geodetector and other methods and spatial technologies to deeply analyze the spatial and temporal evolution of the pseudo human settlements and the driving mechanism of the 14 cities in Liaoning Province from 2011 to 2020. The results show that: 1) Liaoning Province’s pseudo human settlements in the time evolution of the overall quality of the main theme of the rise, with the “Internet festival” node effect and significant stage. 2) The spatial distribution is characterized by the geographical layout of “1″-type high-quality development centers and concentric-circle spatial distribution; and the trend surface shows a low uniformity pattern of “high in the south-central part and low in the surrounding area”. 3) The degree of system coupling and the degree of coupling coordination both show a fluctuating upward trend, with the spatial heterogeneity characteristic of “high in the central part and low in the surrounding area”. 4) Tool system has become the emerging driving force, communication and social chat has become the basic driving force, and life service is the invisible driving force; communication class and community class are the important leading driving factors. The study aims to enrich the research system of human settlements, promote the development of the discipline of human settlements geography, provide a new basis for the construction of human settlements in the new era, and respond to the demand for decision-making in the strategy of network power.